Prevention, Medical Management, and Adjudication of Workplace Injuries: A Thirty-Two Year Follow-up of an Integrated Workers' Compensation Program. Issue 10 (21st October 2021) - Bernacki, Edward J.; Kalia, Nimisha; Soistman, Sharon; Minor, Sebastian A.; Barry, Jill; Lavin, Robert A.; Tao, Xuguang (Grant)
Abstract : Objective: To describe the cost outcomes of an integrated workers' compensation program. Methods: We studied a population that increased from 20K to 59K, incurring 8807 lost-time claims between 1988 and 2020. Results: Lost-time claims decreased from 22.15 to 4.32 per 1000 employees (1988 to 2020), and total closed lost-time claim costs per $100 payroll, decreased from $0.62 to $0.17 (1988 to 2017). The percent of claims resolved within 3 years of the accident increased from 10% to 89% (1988 to 2017). Adjusting for medical inflation and wage increases, total workers' compensation benefits paid per claim decreased $124 per year, medical benefits decreased $45 per year and indemnity benefits decreased $79 per year. Conclusion: On both a population (per employee) and on a per claim basis, workers' compensation costs decreased substantially, which is attributable to improvements in accident prevention and decreases in claim duration.